KONTRIBUSI KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR - arifudin, Arifudin (Tarbiyah, 2014)
Objective of this study are to determine the contribution of job satisfactionon Organizational Citizenship Behavior, contribution of organizational commitment on Organizational Citizenship Behaviorof high school teachers in HuluSungai Utara, either separately or simultaneously. This research uses a survey method with a quantitative approach. Populationin this study was the teacher in Hulu Sungai Utara, with a sample of 120 teachers. The results showed: (1) Job satisfaction contributes to OCB of 26.9% with Freg=43.356 and effective contribution= 18.5%, (2) organizational commitment contributes to OCB of 22.8% with Freg=34.910 and effective contribution = 11.7%, and (3) the contribution of job satisfactionand organizational commitment to OCB is 30.3% with Freg of 25.417.